Determinants of Tax Avoidance: The Role of Executive Character, Sales Growth, and Firm Size - Sani; Atria Tiffany Widyaningsih (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2026)
Tax avoidance remains a persistent challenge to fiscal sustainability in Indonesia, where tax revenue constitutes the primary source of national development financing. This study investigates the determinants of tax avoidance among real estate and property companies listed on the Indonesia Stock Exchange during the 2019–2023 period. Using a quantitative associative design, purposive sampling yielded nine companies producing 45 firm-year observations. Tax avoidance was measured through the Effective Tax Rate, while executive character was proxied by corporate risk, sales growth by year-over-year revenue change, and firm size by the natural logarithm of total assets. Multiple linear regression analysis was conducted using IBM SPSS version 26. Classical assumption tests confirmed the validity of the regression model. Results show that executive character and firm size each significantly and negatively influence tax avoidance, while sales growth produces no significant effect. Collectively, the three variables explain 29.2% of tax avoidance variance, with the model significant at the one percent level. These findings suggest that behavioral governance and organizational scale are more decisive drivers of corporate tax behavior in Indonesia's property sector than revenue performance alone.